2008
DOI: 10.2174/1874241600801010013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Physical Training and Metformin in Diabetic Rats

Abstract: Diabetes mellitus is a metabolic disease associated with multiple organ damage, dysfunction and failure. Metformin is widely used to treat diabetes, but regular exercise also improves metabolic control in diabetic individuals and has an important role in the management of this disease. In this work, we compared the effects of metformin and physical training in diabetic male Wistar rats. Four groups of rats were used: (n=6 per group): sedentary control (SC), sedentary diabetic (SD), trained diabetic (DT) and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…Our result supports the findings of Silevera et al (2008), that is, blood sugar is reduced and weight is induced in diabetic rats with swimming activity [ 51 ]. The present data were consistent with the findings of Zinman et al (2004) and confirmed the effect of exercise on blood sugar and insulin resistance [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our result supports the findings of Silevera et al (2008), that is, blood sugar is reduced and weight is induced in diabetic rats with swimming activity [ 51 ]. The present data were consistent with the findings of Zinman et al (2004) and confirmed the effect of exercise on blood sugar and insulin resistance [ 52 ].…”
Section: Discussionsupporting
confidence: 93%